Chronic Osteomyelitis of Clavicle in a Neonate: Report of Morbid Complication of Adjoining MRSA Abscess - Shishir Murugharaj Suranigi; Manoj Joshi; Pascal Noel Deniese; Kanagasabai Rangasamy; Syed Najimudeen; James J. Gnanadoss (Case Reports in Pediatrics)
Osteomyelitis of clavicle is rare in neonates. Acute osteomyelitis of clavicle accounts for less than 3% of all osteomyelitis cases. It may occur due to contiguous spread, due to hematogenous spread, or secondary to subclavian catheterization. Chronic osteomyelitis may occur as a complication of residual adjoining abscess due to methicillin resistant staphylococcus aureus (MRSA) sepsis. We report a newborn female with right shoulder abscess that developed chronic clavicular osteomyelitis in follow-up period after drainage. She required multiple drainage procedures and was later successfully managed with bone curettage and debridement. We report this case to highlight that a MRSA abscess may recur due to residual infection from a chronic osteomyelitis sinus. It may be misdiagnosed as hypergranulation tissue of nonhealing wound leading to inappropriate delay in treatment. High index of suspicion, aggressive initial management, and regular follow-up are imperative to prevent this morbid complication.